The Role of Education in Preventing Early Marriage and Impact on Family Law in Indonesia - Bunyamin Yafid; Mujahidin; Winda Sari (Universitas Muhammadiyah Palu, 2025)
The purpose of this study is to analyze the role of education in preventing early marriage in Indonesia, as well as to explore its impact on family law. This study uses a qualitative descriptive method with a normative legal approach to analyze cases of early marriage in Indonesia from the perspective of protecting children's rights. Data were obtained from print media, online media, and previous research, as well as expert opinions and community groups. The conclusion shows that the impact of early marriage on family law shows that even though there are regulations governing the age limit for marriage, this practice is still ongoing and gives rise to various problems, both in terms of law, social, and psychological. Early marriage has the potential to harm the rights of women and children, such as limited access to education, poor health, and the inability to manage a household properly which often leads to divorce. Family law needs to be strengthened, both in terms of supervision, protection of individual rights, and community empowerment, to overcome this problem and ensure that every individual enters marriage at an age that is physically, mentally, and socially mature.